Trenchless renewal of culverts and storm sewers - Osborn, Lynn E. (American Society of Civil Engineers, 2010)
This manual describes technologies used by engineers and transportation professionals in renewing culverts and drainage structures under roads, railroads, airport runways, streets and similar structures. The book covers topics such as safety, cleaning and inspection, condition assessment and evaluation, description of trenchless renewal methods, and lifecycle considerations. The chapter on renewal technologies presents background information, installation procedures, design considerations, installation requirements, asset management and quality assurance/quality control, and inspection requirements. This manual will be valuable to engineers, agencies, consultants, and professionals involved with culvert and storm sewer renewal. -- Provided by publisher.
Keywords: Storm sewers -- Maintenance and repair.; Culverts -- Maintenance and repair.; Pipelines -- Maintenance and repair.; Trenchless construction.; elektronické knihy; electronic books